Tuberculosis-HIV Co-infection: Factors Associated With Its Mortality in Malaysia - Gary Goh Chun Chao; Richard Avoi (Universiti Putra Malaysia, 2023)
About ten million people were diagnosed with Tuberculosis (TB) in 2019. It has been one of the top ten causes of death worldwide with 1.4 million recorded cases, and 15% of them were people with Human Immunodeficiency Virus (HIV). This study aims to identify factors associated with mortality among patients with TB-HIV co-infection in Malaysia. Methods: A retrospective cohort study was conducted using secondary data from the TB Information System (TBIS) in Malaysia from 2015 to 2019. A Kaplan-Maier survival curve and a Cox regression analysis were applied. Results: The factors associated with mortality among TB-HIV co-infection patients regarding foreign nationality include no level of education, no directly observed therapy (DOT) supervision, passive case detection, far-advanced findings on chest radiography, no highly active antiretroviral therapy (HAART), and no co-trimoxazole preventive therapy (CPT) treatment. Conclusion: The above findings provide a better picture of the current situation of TB-HIV co-infection on a national level. Therefore, the Ministry of Health Malaysia should give more focus and priority to addressing the challenge of reducing the dual burden disease of TB and HIV in Malaysia.